2021
DOI: 10.1002/vms3.618
|View full text |Cite
|
Sign up to set email alerts
|

Applied anatomy of the skull in the Arabian horse: A computed tomographic, cross‐sectional, volumetric and morphometric study

Abstract: This study was conducted to present a comprehensive and integrative computed tomography (CT) -anatomical cross sections atlas of skull, volumetric properties of the paranasal sinuses, and morphometric values for surface cranial nerves in the adult Arabian horse. Ten heads of Arabian horse breed were used. The different structures in the nasal, oral and cranial cavities were determined and labelled in the anatomical sections and their corresponding CT scan images. Three paranasal sinuses namely maxillary, conch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…In horses, the sphenoid sinus initially resides in the presphenoid bone, later extending to the basisphenoid bone with age. The sphenoid sinus typically merges with the palatine sinus to create the sphenopalatine sinus in horses (Bahar et al, 2014;Brinkschulte et al, 2013;Goodarzi et al, 2021;Köhler et al, 2021;Schummer et al, 1979) and is infrequently absent (Schummer et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In horses, the sphenoid sinus initially resides in the presphenoid bone, later extending to the basisphenoid bone with age. The sphenoid sinus typically merges with the palatine sinus to create the sphenopalatine sinus in horses (Bahar et al, 2014;Brinkschulte et al, 2013;Goodarzi et al, 2021;Köhler et al, 2021;Schummer et al, 1979) and is infrequently absent (Schummer et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, the sinus is substantial and extends to the temporal, occipital and palatine bones (Hillmann, 1975). In horses, the sphenoid sinus typically merges with the palatine sinus, forming the sphenopalatine sinus (Bahar et al, 2014;Brinkschulte et al, 2013;Goodarzi et al, 2021;Köhler et al, 2021). In buffaloes, Moustafa and Kamel (1971) and Alsafy et al (2013) identified the sinus, while Farag et al (2017) reported its absence.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike some of the earlier reports, 2–4,13,17,19,21 it was reported in buffalo 20,26 and Egyptian sheep 18 that the dorsal conchal sinus communicates with the rostral frontal sinus. Similarly, in horses, this sinus is fused with the frontal sinus through a wide opening and opens into the middle nasal meatus through the maxillary sinus 1,3 , 8,9,11 . In the Holstein cow, the dorsal conchal sinus opens into the rostral frontal sinus like in buffaloes, Egyptian sheep, and horses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in horses, this sinus is fused with the frontal sinus through a wide opening and opens into the middle nasal meatus through the maxillary sinus. 1,3,8,9,11 In the Holstein cow, the dorsal conchal sinus opens into the rostral frontal sinus like in buffaloes, Egyptian sheep, and horses. Thus, it communicated indirectly with the ethmoidal meatus in the caudal part of the nasal cavity via the rostral frontal sinus (Figure 3C/h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation